The Characteristics of Demineralized Dentin Material Sponge as Guided Bone Regeneration Based on the FTIR and SEM-EDX Tests - Mulyawan, Indra; Danudiningrat, Coen Pramono; Soesilawati, Pratiwi; Aulanni'am, Aulanni'am; Yuliati, Anita; Suroto, Heri; Bramantoro, Taufan; Rizqiawan, Andra; Moon, Seong-Yong (European Journal of Dentistry, 2022)
Objective The objective of this study was to determine the characteristics of demineralized dentin material sponge (DDMS).Material and Methods An observational study was conducted on DDMS and BPCM. Fourier transform infrared (FTIR) test was performed to determine the characterizations of the materials. Scanning electron microscope-electron dispersive X-ray spectroscopy (SEM-EDX) test was performed to observe the elements contained in the materials.Results The infrared spectrum of the DDMS and BPCM functional groups showed the same pattern in each variation, and no significant differences were found. According to SEM analysis, the cavities that make up the membrane were spotted on the surface. Besides, according to the SEM-EDX analysis, DDMS contained chlorine, carbon, and calcium, while BPCM contained carbon, oxygen, and sulfur.Conclusion DDMS has the potential to be a biomaterial for bone tissue engineering in terms of the characteristics. DDMS had a structure that almost resembles BPCM as seen from the results of the FTIR graph between DDMS and BPCM. The morphological structure of the two materials in the SEM test appeared to have porosity with various sizes.
Keywords: tissue engineering; guided bone regeneration; demineralized dentin; Fourier transform infrared; SEM-EDX